DETERMINATION OF COST OF PRODUCTION Activity Based Costing SYSTEM WITH BAMBOO CRAFT ON INDUSTRY karti AJI - Ariyanto, Harnawan; Kholisoh, Dr. Luluk (Accounting, 2009)
Intense competition in the business world today forced the management of the company / industry to consider carefully the cost of products for the products they produce. Moreover Indonesia entered the Asian free trade area in which the level of competition not only from within the country but include competition from other countries. This forced the industry / firms examine the procedures used for determining cost. Determining the selling price of the product must take into account that accurate product costs, because of good cost analysis will reflect a good decision. From the calculation of production costs imposed by bamboo handicraft companies Karti Aji (traditional system) and the cost of production according to the author (ABC system) there are several conclusions, namely: So far the company Karti Aji bamboo handicraft factory overhead charge into a product with an allocation of raw materials by using the estimates. Thus the production cost calculation becomes less accurate. Error in determining the cost of production will affect the level of company profits, because firms can not compete in terms of determining the cost of goods manufactured Keywords : cost of production, activity based costing system